Design and Construction of an Interactive Intelligent Learning System for English Learners in Higher Education Institutions - Ping Chen (Advances in Multimedia, 2022)
At present, the traditional teaching mode of English teaching in higher vocational institutions is not compatible with the characteristics and teaching objectives of higher vocational education under the new situation. The rapid development of interactive multimedia technology has brought a new teaching style and experience to English basic education. Interactive teaching mode breaks the shackles of traditional teaching mode and focuses on cultivating students’ English language application ability and communicative ability. By using interactive multimedia technology, to begin with, students can improve their English communicative ability more effectively in several aspects, including stimulating their interest in speaking, creating an English-speaking environment, and mobilizing their subjective initiative, and can organically integrate with the learning of professional knowledge to lay a foundation for employment. This paper proposes an interactive intelligent learning system based on artificial intelligence algorithms. This new English teaching system with the interaction theory realizes the transformation of a new student-centered teaching mode, which is a great contribution to English classroom learning in higher education institutions.